Periodontitis, dental plaque, and atrial fibrillation in the Hamburg City Health Study - Struppek, Julia; Schnabel, Renate B.; Walther, Carolin; Heydecke, Guido; Seedorf, Udo; Lamprecht, Ragna; Smeets, Ralf; Borof, Katrin; Zeller, Tanja; Beikler, Thomas; Börschel, Christin S.; Karakas, Mahir; et al. (PloS one, 2021)
Atrial fibrillation (AF) is a major health problem and causes heart failure and stroke. Pathophysiological mechanisms indicate a link with oral health including periodontitis (PD), but supporting data are scarce. The aim was to investigate the link between features of oral health and the prevalence of AF. This cross-sectional analysis of the Hamburg City Health Study included 5,634 participants with complete data on their PD and AF status. AF was assessed via self-reported questionnaire or medically diagnosed by standard 12-lead resting ECG. The oral health examination included full-mouth measurements of the dental plaque index (PI), the clinical attachment loss (CAL) at 6 sites per tooth, the bleeding on probing (BOP) and the decayed, missing and filled teeth (DMFT) index. Descriptive analyses for all variables stratified by the status of PD were performed. To test for an association between prevalent PD and prevalent AF, multivariable logistic regression models were used. Mediation analysis was used to test if interleukin-6 (IL-6) and/or C-reactive protein (CRP) mediated the association between PD and AF. Atrial fibrillation (prevalence: 5.6%) and the severity of PD (prevalence: moderate: 57.7%, severe: 18.9%) increased with age in men and women. Prevalent severe PD, CAL ≥3 mm, PI, and BOP were all associated with prevalent AF in unadjusted regression analysis. However, no association except for PI (odds ratio (OR): 1.22, 95% confidence interval (CI): 1.1-1.35, p<0.001) could be observed after adjusting for age, sex, high-sensitivity C-reactive protein (hs-CRP), interleukin-6 (IL-6), body mass index, diabetes, smoking, and educational level. Participants brushing their teeth at least twice daily had a lower AF prevalence compared with those brushing only once daily. Hs-CRP, IL-6, and the odds of AF increased as a function of PD severity grades in unadjusted analysis. However, neither the DMFT index nor IL-6 or CRP was associated with AF after adjusting for age and sex. Mediation analyses could not provide support for the hypothesis that IL-6 or CRP acted as mediator of the association between prevalent PD and prevalent AF. The study shows an association between prevalent AF and increased dental plaque levels indicated by a higher PI. In contrast, an association of prevalent PD with prevalent AF after adjustments for several confounders could not be demonstrated. Further studies are necessary to investigate the mechanisms underlying poor oral hygiene and AF as well as the influence of improved oral hygiene on AF onset.